Interventions to mitigate the risks of COVID-19 for people experiencing homelessness and their effectiveness: a systematic review - Obianuju Ogbonna; Francesca Bull; Bethany Spinks; Denitza Williams; Ruth Lewis; Adrian Edwards (Frontiers Media S.A., 2024)
ObjectivesPeople experiencing homelessness also experience poorer clinical outcomes of COVID-19. Various interventions were implemented for people experiencing homelessness in 2020-2022 in different countries in response to varied national guidance to limit the impact of COVID-19. It is important to understand what was done and the effectiveness of such interventions. This systematic review aims to describe interventions to mitigate the risks of COVID-19 in people experiencing homelessness and their effectiveness.MethodsA protocol was developed and registered in PROSPERO. Nine databases were searched for studies on interventions to mitigate the impact of COVID-19 on people experiencing homelessness. Included studies were summarised with narrative synthesis.ResultsFrom 8,233 references retrieved from the database searches and handsearching, 15 were included. There was a variety of interventions, including early identification of potential COVID-19 infections, provision of isolation space, healthcare support, and urgent provision of housing regardless of COVID-19 infection.ConclusionThe strategies identified were generally found to be effective, feasible, and transferable. This review must be interpreted with caution due to the low volume of eligible studies and the low quality of the evidence available.